POLITIK RAKYAT KAMPUNG DI KOTA SURABAYA AWAL ABAD KE-20 - Purnawan Basundoro (SASDAYA: Gadjah Mada Journal of Humanities, 2016)
This article aims to explain the politics activities by the villagers in Surabaya at the early of 20th century. The villagers was always considered as the passive people who refused to be involved in a conflict, therefore didn’t do the politic. The historic methodology is taken in this research by referring to the documents from the same century, the newspaper in Surabaya, and also referring to other tertiary resources. The approach chosen is the politic history, a history to describe the struggle of the people to achieve their will. The villagers had various strategy and tactic. As for the villagers who already had the experience of education, even though it was only a basic education, they wrote so many protests in the newspaper related to the decisions of the colonial government which were not in their favour. There was a newspaper in Surabaya managed by the indigenous people at that time, middle scale, and eager to gather all the complaint from the low class society. They also protested directly to the government by using the politic organisation. The formal gathering held by the member of the gemeenteraad, known as “begandring”, was used by the villagers to speak up their aspiration.